Kajiado Smallholder Women Farmers’ Training: Participatory Integrated Climate Services for Agriculture (PICSA) - Jelagat, Joyce; Koech, Eunice; Ouya, Melissa; Seid, Hussen (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate change and variability in Kenya pose significant challenges for agricultural decision-making due to erratic rainfall patterns, especially over the Arid and Semi-Arid Lands (ASALS). The agriculture value chain carries a wide range of actors, with both men and women being highly involved. Women play a crucial role in agriculture, contributing a significant portion of the food supply. However, gender roles limit their capacities, and they need help accessing essential resources, information, and technologies that could bolster their productivity and resilience in the face of climate change. Providing accurate climate and weather information is essential to aid in their decision-making processes. Additionally, there is a noticeable gender disparity in the involvement of women and youth in decision-making forums related to climate services, hindering their access to crucial information and decision-making power. One approach to closing this gap is to facilitate Participatory Integrated Climate Services for Agriculture (PICSA) sessions where women smallholder farmers collaborate with climate information experts to undertake tailored agrometeorological decisions based on climate forecasts. ICPAC, with support from the AICCRA project, held PICSA training for women smallholder farmers in Kajiado county, bringing together women from five groups: Euwaso Widows Women Group, Naiposho Women Group, Matonyok Women Group, and Ewamu Women Group, with the Rural Women Farmers Group serving as the umbrella group. These women engage in various livelihood activities, including kitchen gardening, livestock keeping, poultry farming, and beadwork. The Maasai women follow a patriarchal system that influences their roles and decision-making. As a pastoralist community, educating women farmers on agriculture is necessary as a potential alternative or supplementary livelihood. The three-day workshop featured in-depth discussions on roles and responsibilities, resource mapping, livelihood options, developing seasonal calendars, and the utilization of climate information in decision-making to enhance agricultural productivity. The forum commenced with an opening address from Dr. Hussen Seid, the AICCRA project focal point, who warmly welcomed all participants and expressed gratitude for their commitment to attending the training despite cultural norms that may hinder women's education and empowerment. Dr. Seid provided an overview of ICAPC's objectives and highlighted additional initiatives supported by the AICCRA project. Emphasizing the potential benefits of the training in enhancing farming practices and increasing productivity, he encouraged participants to remain engaged and actively participate in the sessions.